2023
DOI: 10.1093/pnasnexus/pgad002
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylation regulates de novo shoot regeneration

Abstract: During de novo plant organ regeneration, auxin induction mediates the formation of a pluripotent cell mass called callus, which regenerates shoots upon cytokinin induction. However, molecular mechanisms underlying transdifferentiation remain unknown. Here, we showed that the loss of HDA19, a histone deacetylase (HDAC) family gene, suppresses shoot regeneration. Treatment with an HDAC inhibitor revealed that the activity of this gene is essential for shoot regeneration. Further, we identified target genes whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…This difference between roots and shoots for compounds 2 and 3 could be attributed to HDA action, which is more involved in the regulation of de novo shoot generation and formation rather than root control. According to Ma et al and Temman et al, roots are also affected by HDA action, but their effects are more focused on root epidermis formation and hair induction than elongation or generation [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…This difference between roots and shoots for compounds 2 and 3 could be attributed to HDA action, which is more involved in the regulation of de novo shoot generation and formation rather than root control. According to Ma et al and Temman et al, roots are also affected by HDA action, but their effects are more focused on root epidermis formation and hair induction than elongation or generation [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the regulatory network instructing fate changes during regeneration is mediated by both auxin and changes in chromatin status (X. Liu et al, 2023;Temman et al, 2023;Tenea et al, 2009;Zheng et al, 2009). Identifying date palm-specific regeneration factors and their regulation will help in understanding the regeneration process in date palm.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that plant morphogenesis in vitro has an epigenetic mechanism similar to that of plants [ 171 ]. Epigenetic regulation includes dynamic changes in DNA methylation, histone modification, chromatin accessibility, and other processes that determine the transition of somatic cells to embryogenesis [ 166 , 172 , 173 ]. However, “direct epigenetic regulators” were rarely used in PTC since during morphogenesis, the process of DNA methylation/histone modification is very dynamic and, in many cases, it occurs differently in different types of plant cells during embryo/shoot induction [ 172 ].…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%
“…However, “direct epigenetic regulators” were rarely used in PTC since during morphogenesis, the process of DNA methylation/histone modification is very dynamic and, in many cases, it occurs differently in different types of plant cells during embryo/shoot induction [ 172 ]. As an example, we can cite [ 173 ], which claimed that mutation in the histone deacetylases (HDAC) gene inhibited plant regeneration. This is very logical since histone hyperacetylation is required only for the formation of an organizer stem cell niche, and thereafter, histone performs deacetylation to form leaf primordia.…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%